Efficacy and Safety of Dupilumab in Moderate-to-Severe Bullous Pemphigoid - Zhang, YiHua; Zhang, Jing; Chen, JiaWen; Xu, QiuYun; Zou, Ying; Chao, Ji (Frontiers in Immunology, 2021)
Abstract: Background: Bullous pemphigoid (BP) is an autoimmune blistering disorder that predominantly affects the elderly. As the main treatment for BP, systemic corticosteroids are often limited by their side effects. Safer treatment modalities are therefore needed. Dupilumab is a biologic agent used to treat BP in recent years. Methods: Medical records of patients with moderate-to-severe BP were retrospectively reviewed. Twenty-four patients were included (follow up period: 32 weeks), eight of whom received dupilumab in combination with methylprednisolone and azathioprine (dupilumab group) while the other 16 patients received methylprednisolone and azathioprine (conventional group). Response to dupilumab was evaluated by comparison of several parameters (time to stop new blister formation, time to reduce the systemic glucocorticoids to minimal dose, and total amount of methylprednisolone). Results: The median age of patients in the dupilumab group and the conventional group were 64.50 years (range: 22-90 years) and 64.50 years (range: 17-86 years), respectively. The median duration of disease before admission in the dupilumab group was 2 months (range: 1-240 months), and 2.5 months (range: 1-60 months) in the conventional group. The median time to stop new blister formation was 8 days (range: 1-13 days) and 12 days (range: 5-21 days) in patients of the dupilumab group and conventional group, respectively (P=0.028). In addition, the median time to reduce the systemic glucocorticoids to minimal dose (methylprednisolone 0.08 mg/kg/day) was 121.5 days and 148.5 days for the dupilumab group and conventional therapy group, respectively (P=0.0053). The median total amount of methylprednisolone (at the time of reaching the minimal dose) used in the dupilumab group was 1898 mg (range: 1624-2932 mg) while the cumulative dose of conventional group was 2344 mg (range: 1708-4744 mg) (P=0.036). The median total amount of azathioprine (at the time of reaching the minimal dose) used in dupilumab group was 8300 mg (range: 7100-10400 mg) while the total dose of conventional group was 10300 mg (range: 8900-14400 mg) (P=0.0048). No adverse event related to dupilumab was recorded. Conclusions: Dupilumab in addition to methylprednisolone and azathioprine seems superior to methylprednisolone /azathioprine alone in controlling disease progression and accelerating the tapering of glucocorticoids.